TTRMDB: A database for structural and functional analysis on the impact of SNPs over transthyretin (TTR) using bioinformatic tools. (August 2020) - Srinivasan, E.; Natarajan, Nandhini; Rajasekaran, R.
Graphical abstract: Highlights: Hereditary Transthyretin-associated amyloidosis (ATTR) caused by mutations in transthyretin (TTR). More than 100 distinct mutations in TTR protein are reported. Pathogenic effect of TTR mutant remain unanswered in structural level. Mutational effect in TTR concerning stability, functionality and aggregation propensity were predicted. A curated database (TTRMDB) is developed to provide free access of all the mutational data. Abstract: Hereditary Transthyretin-associated amyloidosis (ATTR) is an autosomal dominant protein-folding disorder with adult-onset caused by mutation of transthyretin (TTR). TTR is characterized by extracellular deposition of amyloid, leading to loss of autonomy and finally, death. More than 100 distinct mutations in TTR gene have been reported from variable age of onset, clinical expression and penetrance data. Besides, the cure for the disease remains still obscure. Further, the prioritizing of mutations concerning the characteristic features governing the stability and pathogenicity of TTR mutant proteins remains unanswered, to date and thus, a complex state of study for researchers. Herein, we provide a full report encompassing the effects of every reported mutant model of TTR protein about the stability, functionality and pathogenicity using various computational tools. In addition, the results obtained from our study were used to create TTRMDB (Transthyretin mutant database), which could be easy access to researchers at http://vit.ac.in/ttrmdb .